Functional Characterization and Conditional Regulation of the Type VI Secretion System in Vibrio fluvialis - Huang, Yuanming; Du, Pengcheng; Zhao, Meng; Liu, Wei; Du, Yu; Diao, Baowei; Li, Jie; Kan, Biao; Liang, Weili (Frontiers in Microbiology, 2017)
Vibrio ﬂuvialis is an emerging foodborne pathogen of increasing public health concern. The mechanism(s) that contribute to the bacterial survival and disease are still poorly understood. In other bacterial species, type VI secretion systems (T6SSs) are known to contribute to bacterial pathogenicity by exerting toxic effects on host cells or competing bacterial species. In this study, we characterized the genetic organization and prevalence of two T6SS gene clusters (VflT6SS1 and VflT6SS2) in V. ﬂuvialis. VflT6SS2 harbors three “orphan” hcp-vgrG modules and was more prevalent than VflT6SS1 in our isolates. We showed that VflT6SS2 is functionally active under low (25°C) and warm (30°C) temperatures by detecting the secretion of a T6SS substrate, Hcp. This finding suggests that VflT6SS2 may play an important role in the survival of the bacterium in the aquatic environment. The secretion of Hcp is growth phase-dependent and occurs in a narrow range of the growth phase (OD600 from 1.0 to 2.0). Osmolarity also regulates the function of VflT6SS2, as evidenced by our finding that increasing salinity (from 170 mM to 855 mM of NaCl) and exposure to high osmolarity KCl, sucrose, trehalose, or mannitol (equivalent to 340 mM of NaCl) induced significant secretion of Hcp under growth at 30°C. Furthermore, we found that although VflT6SS2 was inactive at a higher temperature (37°C), it became activated at this temperature if higher salinity conditions were present ( from 513 mM to 855 mM of NaCl), indicating that it may be able to function under certain conditions in the infected host. Finally, we showed that the functional expression of VflT6SS2 is associated with anti-bacterial activity. This activity is Hcp-dependent and requires vasH, a transcriptional regulator of T6SS. In sum, our study demonstrates that VflT6SS2 provides V. fluvialis with an enhanced competitive fitness in the marine environment, and its activity is regulated by environmental signals, such as temperature and osmolarity.